TELAAH TEORITIS TERHADAP KONTRIBUSI HUKUM DALAM PEMBANGUNAN EKONOMI - Benyamin Tungga (Jurnal Aktual Justice, 2018)
The development of the national economy in its achievement is inseparable from the role of the legal sector. Interdeterministis, between economic and law, two things that affect each other. That is, it can also start from the demands of the economic field to the field of law that can serve as a useful contribution to support economic growth. Law as a normative provision has a very important role and function in the field of economy. Scientific writing is intended to describe the legal theory in economic development. The results of the study provide an explanation that the economic system in Indonesia is Pancasila Economic System that was born in the heart of the nation that is Pancasila and UUD-45 and its interpretation. Therefore, the economic system of Pancasila is directly sourced from Pancasila, especially the fifth principle, namely: Social Justice for all Indonesian people and the mandate of Article 27 paragraph (2), Article 33-34 UUD-45 (4th Amendment). The fifth precept explains that all national and state orientations, economic, legal, social and cultural politics, are imbued with a spirit of comprehensive justice and destined for all Indonesians. Thus the legal contribution in the development of the Indonesian economy is a Pancasila economic system supported by the 1945 Constitution and its interpretation.